At the heart of the interoception network: Influence of the parasubthalamic nucleus on autonomic functions and motivated behaviors. (15th February 2022) - Shah, Tanvi; Dunning, Jeffery L.; Contet, Candice
Abstract: The parasubthalamic nucleus (PSTN), a small nucleus located on the lateral edge of the posterior hypothalamus, has emerged in recent years as a highly interconnected node within the network of brain regions sensing and regulating autonomic function and homeostatic needs. Furthermore, the strong integration of the PSTN with extended amygdala circuits makes it ideally positioned to serve as an interface between interoception and emotions. While PSTN neurons are mostly glutamatergic, some of them also express neuropeptides that have been associated with stress-related affective and motivational dysfunction, including substance P, corticotropin-releasing factor, and pituitary adenylate-cyclase activating polypeptide. PSTN neurons respond to food ingestion and anorectic signals, as well as to arousing and distressing stimuli. Functional manipulation of defined pathways demonstrated that the PSTN serves as a central hub in multiple physiologically relevant networks and is notably implicated in appetite suppression, conditioned taste aversion, place avoidance, impulsive action, and fear-induced thermoregulation. We also discuss the putative role of the PSTN in interoceptive dysfunction and negative urgency. This review aims to synthesize the burgeoning preclinical literature dedicated to the PSTN and to stimulate interest in further investigating its influence on physiology and behavior. This article is part of the special Issue on 'Neurocircuitry Modulating Drug and Alcohol Abuse'. Highlights: The parasubthalamic nucleus is embedded in neural circuits mediating interoception and emotions. Parasubthalamic neurons are excitatory and express stress-related neuropeptides. The parasubthalamic nucleus responds to food ingestion, visceral distress, and aversive memories. The parasubthalamic nucleus controls cardiovascular function, thermoregulation, feeding, and impulsivity. Recruitment of parasubthalamic neurons may contribute to negative urgency.